Resveratrol exerts a biphasic effect on apolipoprotein M. (12th November 2015) - Kurano, Makoto; Hara, Masumi; Nojiri, Takahiro; Ikeda, Hitoshi; Tsukamoto, Kazuhisa; Yatomi, Yutaka
Abstract : Background and Purpose: Resveratrol exerts a range of beneficial actions in several areas of pathophysiology, including vascular biology. Here, we have investigated the effects of resveratrol on apolipoprotein M (apoM), a carrier and modulator of sphingosine 1‐phosphate (S1P), a vasoactive lipid mediator. Experimental Approach: We used a hepatoma cell line (HepG2), human primary hepatocytes and C57BL/6 mice. We measured apoM, S1P and related enzymes, LDL receptors and sirtuin1 activity, using Western blotting, RT‐PCR and enzyme assays. We also used si‐RNA to knock‐down sirtuin1 in HepG2 cells. Key Results: In cultures of HepG2 cells, resveratrol (1‐10 μM) increased intracellular apoM and S1P. High concentrations of resveratrol (100 μM) decreased extracellular (in the culture medium) apoM, whereas moderate concentrations of resveratrol (1–10 μM) increased extracellular apoM. High concentrations of resveratrol also increased LDL receptor expression, while all concentrations of resveratrol activated the histone deacetylase sirtuin1. In cultures of human primary hepatocytes, resveratrol, at all concentrations, increased both intra‐ and extracellular apoM. When wild‐type mice were fed a resveratrol‐containing chow (0.3% w/w) for 2 weeks, both the plasma and hepatic apoM and S1P levels were increased. However, the resveratrol diet did not affect hepatic LDL receptor levels in this in vivo study. Conclusions and Implications: Resveratrol increased intra‐ and extracellular levels of apoM, along with intracellular S1P levels, while a high concentration of resveratrol reduced extracellular apoM. The present findings suggest that resveratrol has novel effects on the metabolic kinetics of S1P, a multi‐functional bioactive phospholipid.